Android Controlled Mini Sauna For Animal Laboratory Research Facility Using Arduino Uno - Taufiq, Vegy Luthfian Fendi, Umi Fadlilah, S.T., M.Eng (2016)
Obesity is the accumulation of excessive or abnormal fat so that it can give a bad risk to health. Obesity is included in the major risk factors for a number of chronic diseases including diabetes, heart disease and cancer. It is necessary to obesity therapy that aims to reduce excess fat in the body so that it can restore normal function and metabolic processes of the body organ. The main focus of this study on exposure therapy using the mini steam sauna Arduino-based experiments with mice as objects then the results will be displayed on the android based smartphone via an HC-05 Bluetooth connection designed for laboratory animal research facilities. Arduino is a single-board micro controller is an open-source, derived from Wiring platform, designed to facilitate the use of electronics in various fields. Results of testing the temperature of the final product of this study showed the difference as much as 1.3% from a common digital thermometer. While the maximum distance Bluetooth range suggested is 15 meters. While testing the respondents are given through a questionnaire.